Ministry to Muslim women : longing to call them sisters - Love, Fran, 1952-; Eckheart, Jeleta, 1960- (Pasadena, Calif. : William Carey Library, 2000)
This book is a compilation of real-life experiences by women actively involved in reaching Muslim women for Christ. These articles approach the question of the gospel and Islam from a female perspective. - Publisher.
God's passion released through us / Fran Love -- Current issues affecting Muslim women / C.M. Amal -- Muslim women in crisis / Debi Bartlotti -- Muslim women and the occult : seeing Jesus set the captives free / Julia Colgate -- Islamic reformation and fundamentalism's impact on Muslim women / Diana Colby -- Understanding the spiritual hunger of Muslim women / Lea Ruth -- Why Muslim women come to Christ / Miriam Adeney -- The sword of Christ : Muslim women make a costly commitment / B. Linda Smith -- What helps Muslim women grow in Christ / Iliam -- Discipleship of Muslim background believers through chronological Bible storying / A.H. -- Evangelism to and through family networks / Kay Waters -- Building community in a Muslim background believer church : a case study among Uighur women / Anne Jansen -- Developing women leaders in Muslim background believer churches / Fran Love -- The relationship between the missionary and the agency that sends her : from the perspective of the agency / Mary Ann Cate -- The relationship between the missionary and the agency that sends her : from the perspective of field missionaries / Group discussion -- Why am I here? / Elizabeth Learner -- How can I thrive here? / Karol Downey -- Who is with me here? / Cookie Liverman.
Includes bibliographical references (pages 261-264) and index.
Keywords: Missions to Muslims -- Congresses; Muslim women -- Religious life -- Congresses; Women missionaries -- Islamic countries -- Congresses